RECONSTRUCTING THE EVOLUTIONARY HISTORY OF HANTAVIRUSES - R. Yanagihara (Acta Biomedica Scientifica, 2012)
Segregation of hantaviruses into clades that parallel the molecular phylogeny of rodents (order Rodentia) in the Murinae, Arvicolinae, Neotominae and Sigmodontinae subfamilies suggests that hantaviruses may have co-evolved with their reservoir hosts. Recently, however, host switching and local species-specific adaptation have been proposed, to account for the similarities between host and. virus phylogenies. The demonstration, that Thottapalayam. virus, a hantavirus isolated, from the Asian house shrew (Suncus murinus), represents an early evolutionary divergence from other hantaviruses has spurred, a search, to ascertain if small mammals having shared, ecosystems with, rodents, such, as shrews (order Soricomorpha, family Soricidae) and. moles (family Tal-pidae), as well as bats (order Chiroptera), may have figured prominently in the evolution and. diversification of hantaviruses. Archival tissues from 1,258 shrews (47 species), 152 moles (10 species) and. 329 bats (32 species), captured, in Europe, Asia, Africa and. North. America in 1980-2012, were analyzed, for hantavirus RNA by RT-PCR. The realization, that newfound, hantaviruses detected, in soricomorphs are genetically more diverse than those harbored, by rodents suggests that the evolutionary history of hantaviruses is more ancient and. complex than previously conjectured and. that ancestral rodents may not have been the original mammalian hosts of primordial hantaviruses.